2020
DOI: 10.3892/or.2020.7910
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑34a‑5p serves as a tumor suppressor by regulating the cell motility of bladder cancer cells through matrix metalloproteinase‑2 silencing

Abstract: Bladder cancer (BC), a common urologic cancer, is the fifth most frequently diagnosed tumor worldwide. hsa-miR-34a displays antitumor activity in several types of cancer. However, the functional mechanisms underlying hsa-miR-34a in BC remains largely unknown. We observed that hsa-mir-34a levels were significantly and negatively associated with clinical disease stage as well as regional lymph node metastasis in human BC. In a series of in vitro investigations, overexpression of hsa-miR-34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…Importantly, miR-34a inhibited cell migration and invasion by also silencing MMP2 expression, interrupting MMP2-mediated cell motility [82]. These results are in line with our previous data demonstrating the ONC capability to decrease MMP2 activity and motility of A375 cells [17].…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, miR-34a inhibited cell migration and invasion by also silencing MMP2 expression, interrupting MMP2-mediated cell motility [82]. These results are in line with our previous data demonstrating the ONC capability to decrease MMP2 activity and motility of A375 cells [17].…”
Section: Discussionsupporting
confidence: 91%
“…To assess the prognostic value of MMP2 and MMP9 expression in patients with BC, we investigated the associations between MMP2 and MMP9 expression and OS. In our previous study, the high MMP2 expression observed in patients with BC was correlated with poor OS [ 27 ]; however, MMP9 showed no such effect (Fig. 3F ).…”
Section: Resultsmentioning
confidence: 67%
“…Furthermore, MMPs not only degrade ECM but also play crucial roles in mediating tumor angiogenesis, metastasis, and invasion. Among the MMP family, MMP-2 promotes tumor growth, tissue invasion, angiogenesis, and metastasis [ 44 46 ], and its overexpression might be associated with tumor progression and a poor prognosis for ovarian epithelial carcinoma, oral cavity cancers, and non-small cell lung cancer patients [ 47 50 ]. Therefore, MMP-2 is considered a potential tumorigenesis biomarker, a key effector of ECM remodeling, and a potential target for antitumor therapy.…”
Section: Discussionmentioning
confidence: 99%